FORMATION OF PROFESSIONAL-CULTURAL RELATIONSHIPS IN FUTURE PHYSICAL EDUCATION TEACHERS (EXAMPLE OF KURASH) - A. Tilakov (Galaxy International Interdisciplinary Research Journal, 2022)
One of the factors determining the rapid development of the struggle, which has been inherited from our ancestors to us as a value, and its prospects, is the issue of personnel. Although the history of wrestling goes back 3-3.5 thousand years, the period of the main development of wrestling corresponds to the 60-70s of the last century. Due to insufficient attention to wrestling in those years, we see that elements of physical education were partially used in the processes of lessons.